Complaint as ‘Sticky Data’ for the Woman WPA: The Intellectual Work of a WPA’s Emotional and Embodied Labor - Anna Sicari (Journal of the Assembly for Expanded Perspectives on Learning, 2020)
There is rich scholarship on emotions in writing program administration, and the labor this work requires from WPAs (Holt; Micciche; McKinney et. al; Ratcliffe and Rickley; Vidali) and on the feminized nature of writing programs and the way gender informs this type of emotional work (Enos; Flynn; Miller; Schell). Many WPA scholars advocate that our administrative work is intellectual work, yet little attention has been given to the emotional and embodied labor of WPA work as intellectual and as defining components of WPA work. Drawing from Sara Ahmed’s recent work on complaint and data I collected from thirty interviews with women WPAs in a two-year IRB approved qualitative study, I bring attention to the emotional and embodied knowledge of WPAs and the need to take more seriously this issue of complaint as a scholarly topic and source of knowledge. Through insight from this archive of complaint stemming from the institutional stories told by the participants, I will explore how critical attention to the embodied experiences of the people doing the work (WPAs) is necessary scholarly work, particularly for feminist scholars and activists who wish to work toward institutional change.
Keywords: Education; Emotional Labor; Writing Programs; Creative Writing; Gender